مفهوم التوحيد في الموروث الفكري لسيد قطب - Hamad Abdulsalam Hamad Alfarisi; Fatmir Shehu; Zainab Bubakr Hamad Zubi (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2023)
Sayyid Qutb was characterized by the attributes of a man who is a thinker, intellectual, literary researcher, patient, and is sincere and honest. And his thought emanating from the establishment of religion and the world on the basis of the Islamic faith had a great impact in enriching the dynamic jurisprudence of the Islamic nation. Sayyid Qutb presented to the Islamic world in particular and to the world in general the true meaning and the concept of the monotheism (Tawhid). This paper aims to present the concept of Tawhid according to what is found in the intellectual legacy of Sayyid Qutb. Furthermore, to stress on its impact on shaping Muslim’s mindset in the modern era.